Methaphors and activity - Mey, Jacob L. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This paper considers metaphor as a kind of activitu in the spirit of Levinson's 'Activity Types' or of Mey's 'Pragmatic Acts'. Contrary to what has been suggested in the literature, mataphors neither belong exclusively to the domain of abstract reasoning (such as by analogy; Max Black), nor are they merely linguistic and/or psychological processes (of cognition: George Lakoff). Methaphors do not originate and live in the brain only, neither do they exclusively belong to some conceptual domain from which they can establish relations to other domains, or blend whit them. Methaphors are primarily pragmatic activities. In my contribution, I will concentrate on the pragmatics of what is called 'embodiment': while metaphors represent, respectively support or illustrate, an activity that id performed by the total human being, the body part of the metaphoric deal is often neglected. Yet, as many researchers in the humanities and the sciences have shown, the role of the body in solving problems through appropriate metaphoring cannot be overestimated. An embodied perspective on thought, and especially on metaphor, will allow us to form a better understanding of the things we do with words, when we use words to do things.